2015
DOI: 10.1112/s0010437x15007423
|View full text |Cite
|
Sign up to set email alerts
|

Growth of in towers for isogenous curves

Abstract: Abstract. We study the growth of X and p ∞ -Selmer groups for isogenous abelian varieties in towers of number fields, with an emphasis on elliptic curves. The growth types are usually exponential, as in the setting of 'positive µ-invariant' in Iwasawa theory of elliptic curves. The towers we consider are p-adic and l-adic Lie extensions for l = p, in particular cyclotomic and other Z l -extensions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…For one application, seeČesnavičius' work on the parity conjecture [2, §5]. [1], [18], [9], [6], [12] and [8]. Table 1 summarises our results for the valuations of minimal discriminants δ, δ of E, E , their Tamagawa numbers c, c , Kodaira types and the leading term φ * ω ω of φ on the formal group (see §1.1 for the notation).…”
Section: Introductionmentioning
confidence: 97%
“…For one application, seeČesnavičius' work on the parity conjecture [2, §5]. [1], [18], [9], [6], [12] and [8]. Table 1 summarises our results for the valuations of minimal discriminants δ, δ of E, E , their Tamagawa numbers c, c , Kodaira types and the leading term φ * ω ω of φ on the formal group (see §1.1 for the notation).…”
Section: Introductionmentioning
confidence: 97%
“…Even in the case where A is defined over Q, and A has complex multiplication, we see that there is an example of this phenomenon; see [4,Remark 1.10]. Here it is shown that the curve 49A2, which has complex multiplication by the order Z[ √ −7], has unbounded 2-part of X in the cyclotomic Z q -extension of Q, for all primes q = 2.…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, when the elliptic curve is not defined over the imaginary quadratic field K over which A has complex multiplication, then other curves with this phenomenon are easy to construct. For instance, in [4,Remark 1.10], the Dokchitsers give a curve A defined over Q(μ 20 ) with complex multiplication by Z + 5 · Z[ √ −1] such that, for all primes q and all Z q -extensions L ∞ /Q(μ 20…”
Section: Introductionmentioning
confidence: 99%
“…Points (ii) and (iii) were motivated by, respectively, Iwasawa theoretic considerations (see [5] Thm. 5.5) and applications to the p-parity conjecture that require knowing the behaviour of Birch-Swinnerton-Dyer quotients up to rational squares in field extensions (see §1.3 below, and §3.4).…”
Section: Introductionmentioning
confidence: 99%
“…However, the semistability assumption is necessary to obtain such a stable growth: for example, the Tamagawa number of the elliptic curve 243a1 fluctuates between 1 and 3 in the layers of the cyclotomic Z 3 -tower of Q 3 , see [5] Remark 5.4.…”
Section: Introductionmentioning
confidence: 99%